2012
DOI: 10.1128/iai.05510-11
|View full text |Cite
|
Sign up to set email alerts
|

Pathoadaptive Conditional Regulation of the Type VI Secretion System in Vibrio cholerae O1 Strains

Abstract: The most recently discovered secretion pathway in Gram-negative bacteria, the type VI secretion system (T6SS), is present in many species and is considered important for the survival of non-O1 non-O139 Vibrio cholerae in aquatic environments. Until now, it was not known whether there is a functionally active T6SS in wild-type V. cholerae O1 strains, the cause of cholera disease in humans. Here, we demonstrate the presence of a functionally active T6SS in wild-type V. cholerae O1 strains, as evidenced by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 58 publications
6
123
1
Order By: Relevance
“…3A and B). It was previously reported that Hcp is increased in cells grown at 23°C compared to levels at 37°C (48), further corroborating our results. A molecular mechanism by which hcp transcription is decreased at 15°C is yet to be determined.…”
Section: Discussionsupporting
confidence: 82%
“…3A and B). It was previously reported that Hcp is increased in cells grown at 23°C compared to levels at 37°C (48), further corroborating our results. A molecular mechanism by which hcp transcription is decreased at 15°C is yet to be determined.…”
Section: Discussionsupporting
confidence: 82%
“…The genes coding for the T6SS apparatus are located in one main cluster (VCA0105 to VCA0124) and two auxiliary clusters (VCA0017 to VCA0022 and VC1415 to VC1421) (21,25). The genes of the T6SS are negatively regulated by the global regulator TsrA, the quorumsensing (QS) regulator LuxO, and the osmolarity-responsive transcriptional regulator OscR, and they are positively regulated by HapR, cyclic AMP receptor protein (CRP), response regulator VxrB, and VasH (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…To this end, the secretion of the very-well-characterized T6SS effector, Hcp, was analyzed. A normal VipA-VipB interaction is an absolute requirement for Hcp secretion since VipA variants that are unable to bind to VipB efficiently do not support secretion of Hcp (26,34). KS100, KS200, and the analogues were serially diluted to final concentrations of 50 M, 100 M, or 200 M and incubated with V. cholerae V52 for 4 h. Extracts from the cells and culture supernatants were examined by Western blotting, and a dose-dependent inhibition of Hcp secretion was observed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The VipA-VipB interaction is an absolute prerequisite for the function of the T6S, and, thus, it would be postulated that the inhibition of the interaction will lead to the abrogation of Hcp secretion or phospholipase activity, both shown to be important T6SS effector mechanisms (28,34). In fact, numerous studies have demonstrated not only a close link between T6SS and bacterial secretion, necessary for virulence, but also the structural roles of VipA, VipB, and Hcp in the needle-like structure required for secretion (2, 4, 13, 14, 27-29, 34, 39, 53, 60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation